2018
DOI: 10.1139/cjz-2017-0343
|View full text |Cite
|
Sign up to set email alerts
|

Fine- and coarse-scale movements and habitat use by Wood Turtles (Glyptemys insculpta) based on probabilistic modeling of radiotelemetry and GPS-telemetry data

Abstract: Understanding animal movement and habitat use is critical for the delineation of habitat requiring protection for species at risk. Defining critical habitat requires studies with observations at a fine enough scale to reflect how animals use and move among habitats and include enough individuals to generalize findings to the population. We present results of a multiyear study on 48 adult Wood Turtles (Glyptemys insculpta (Le Conte, 1830)) from two different populations monitored with low-frequency radiotelemet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 42 publications
(57 reference statements)
2
3
0
Order By: Relevance
“…Even though forested habitat is abundant in the landscape, it was one of the least used cover types. This is similar to findings by Thompson et al (2018). Habitat data were only collected in 2019.…”
Section: Fine-scale Habitat Selectionsupporting
confidence: 89%
See 1 more Smart Citation
“…Even though forested habitat is abundant in the landscape, it was one of the least used cover types. This is similar to findings by Thompson et al (2018). Habitat data were only collected in 2019.…”
Section: Fine-scale Habitat Selectionsupporting
confidence: 89%
“…Similar patterns were also found in Pennsylvania (Kaufmann 1992), West Virginia (McCoard et al 2016, and Ontario (Thompson et al 2018). These findings are informative for northern New England given the prominent timber industry.…”
Section: Movement Patternssupporting
confidence: 64%
“…did affect HR. We note that we were unable to test whether the study length or number of locations/individual affected HR size; however, we suggest that the raw data from an unusually long-term study with very large sample sizes (e.g., [21,45]) or novel studies using current GPS-tracking technology create samples that vary frequently and with high accuracy (e.g., [75,76]) could be sub-sampled to address these questions, as well as to address important issues of spatial autocorrelation. As shown in this study, meta-analysis is a powerful tool that can detect large-scale patterns across studies and provide evidence for or against conclusions made about species within individual studies.…”
Section: Discussionmentioning
confidence: 83%
“…Most previous studies on wood turtle terrestrial habitat relationships have focused on individual‐level habitat use and selection (Kaufmann 1992, Tingley et al 2010, Thompson et al 2018). Collectively, these studies indicate that wood turtles are most often found in open canopy and edge habitats within primarily forested systems, suggesting that terrestrial habitat selection is non‐random (Compton et al 2002, Arvisais et al 2004, Brown et al 2016, Wallace et al 2020).…”
mentioning
confidence: 99%